PENGEMBANGAN KOMIK BERBAHASA JAWA BERMUATAN PARIBASAN UNTUK SISWA SMP DI KABUPATEN KEBUMEN - priyaningsari, septiana (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2016)
The Javanese-speaking comics containing paribasan (proverb) in Kebumen regency is minimum. Whereas, this kind of comics is needed by students. Therefore, this article discusses about what students need from Javanese-speaking comics, how prototype of Javanese-speaking comics are formed, and how Javanese-speaking comics are legalized. The purpose of this research are to comprehend students need toward Javanese-speaking comics, arrange the prototype of Javanese-speaking comics, and describe the result of prototype of Javanese-speaking comics legalizing. The method used in this article is research and development. The technique is descriptive analysis obtaining Javanese-speaking comics containing paribasan in Kebumen accordance with students and teacher’s needs. This comic contains of pictured story with paribasan inside. After comics are created, they will be tested. Then, they will be revised accordance with the suggestion from expert. The revision is reviewed from: (1) content, (2) delivering, (3) linguistics.